Inkulturasi Iman Kristen melalui Musik Tradisional: Kajian Teologi Kontekstual Model Antropologis pada Gereja Kalimatan Evangelis (GKE) di Katingan - Angelika Natalycia; Rhema Y Rosemary Sanggew; Novia Crista Febrianti; Rohit Rohit; Sarmauli Sarmauli (Nubuat : Jurnal Pendidikan Agama Kristen dan Katolik, 2026)
This research examines the process of inculturating the Christian faith thru the use of traditional Dayak Katingan music in church life at the Evangelical Church of Kalimantan (GKE) using the Anthropological Model of Contextual Theology perspective. The research is motivated by the church's need to present expressions of faith that are relevant to the local cultural context without diminishing the essence of Christian teachings. The method used is descriptive qualitative research with a case study approach. Data were obtained thru observation, in-depth interviews, and documentation involving pastors, music ministers, church council members, and congregation members in the Katingan region. The research results show that the use of traditional musical instruments such as japen, suling balawung, and katambung is a form of inculturation that preserves local cultural elements while simultaneously transforming their meaning and function based on Gospel values. In this process, cultural elements that do not contradict Christian teachings are retained and reinterpreted as means of praise, worship, faith expression, and strengthening the congregation's identity. The research findings affirm that the Anthropological Model Contextual Theology enables a constructive dialog between the Gospel and culture, so that traditional music not only serves as a medium for expressing Christian faith but also as a means of preserving Dayak Katingan culture. Thus, the inculturation of traditional music in GKE Katingan contributes to the strengthening of local cultural identity and the deepening of the congregation's spirituality.